Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Section 7.3 - Simplifying Radical Expressions - Exercise Set: 107

Answer

$x^{2}-8x+16$

Work Step by Step

We are given the expression $(x-4)^{2}$, which is equivalent to $(x-4)(x-4)$. We can use the FOIL method to simplify. F=$x\times x=x^{2}$ O= $x\times-4=-4x$ I=$-4\times x=-4x$ L=$-4\times-4=16$ Now, we can add these terms together. $(x-4)^{2}=(x^{2})+(-4x)+(-4x)+(16)=x^{2}-8x+16$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.